Work and technological innovation in organic agriculture - Tereso, M. J. A.; Abrahao, R. F.; Gemma, S. F. B.; Montedo, U. B.; Menegon, N. L.; Guarneti, J. E. [UNESP]; Ribeiro, I. A. (IOS Press, 2012)
Organic agriculture is a sustainable cultivation ecologically, economically and socially. Several researches in organic agriculture have been made from technical perspectives, economic traits or related to ecological aspects. There are practically no investigations into the nature of the technology used in organic agriculture, especially from an ergonomic perspective. From the activity analysis, this study aimed to map the technology used in the production of organic vegetables. Properties producing organic vegetables were selected representing the State of São Paulo. It was applied an instrument (questionnaire and semi-structured interview) with their managers and it was made visual records to identify adaptations, innovations and technological demands that simultaneously minimize the workload and the difficulties in performing the tasks and increase work productivity. For some of the technological innovations a digital scanner was used to generate a virtual solid model to facilitate its redesign and virtual prototyping. The main results show that organic farmers have little technology in product form. The main innovations that enable competitive advantage or allow higher labor productivity occur in the form of processes, organization and marketing.
Keywords: innovation; organic agriculture; horticulture; technological innovation; work productivity